Fundusze unijne w budżecie samorządu terytorialnego - Kołodziejczyk, Danuta (EU Funds in Local Government Finances, 2009)
The article presents and analyzes the diversity of EU-funds within territorial self-government budget. The author states that the level of EU-funds is mostly determined by concentration of socio-economic resources and activities of local authorities in the communities. The proper gaining of EU-funds require decentralization of the financial policy of the community
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 111-118